PENGARUH LITERASI KEUANGAN SYARIAH MASYARAKAT USIA PRODUKTIF TERHADAP PENGUATAN EKONOMI KELUARGA (Studi Kasus Pada Masyarakat Jorong Pakan Sabtu Nagari Panyakalan): (Studi Kasus Pada Masyarakat Jorong Pakan Sabtu Nagari Panyakalan) - Salidar, Salidar; Seflidiana Roza; Rasidah Nasrah (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2023)
This research was conducted on the Jorong Feed community on Saturday Nagari Panyakalan. The purpose of this study was to determine the effect of Islamic financial literacy on strengthening the family economy of the Jorong Pakan Saturday Panyakalan Community. In this study, the population was the Jorong Pakan Saturday Panyakalan Community, which amounted to 225 people with a total sample of 50 people. . With this type of quantitative research and sampling technique using the pourpose sampling method. The data collection technique used is by using a questionnaire/questionnaire. Based on a simple linear regression analysis of the variable Islamic financial literacy of productive age people on the strengthening of the family economy Y=30.213+0.288.X+e. From the t-test performed, the t-count value is greater than t-table 2.224 > 2.010 and the significant level value is 0.031 < 0.05, then H1 is accepted, H0 is accepted. From the Determination Test, the R Square value is 0.093 or 9.3%, this shows that the independent variable has an impact on the dependent variable by 9.3%, while the remaining 90.7% is influenced by other variables not included in this study. for example individual characteristics, discipline, incentives, rewards and family environment.